Penerapan Metode Scrum Pada Sistem Informasi Akuntansi Toko Alat Olahraga - Fajar Agustini; Euis Widanengsih; Henny Destiana (LPPM Universitas Bina Sarana Informatika, 2026)
Accounting management in sporting goods stores often faces challenges such as inefficient manual recording, error-proneness, and delays in presenting financial reports. This situation impacts suboptimal managerial decision-making. This study aims to apply the Scrum method to develop an accounting information system capable of improving the effectiveness of recording and presenting financial reports. The research method uses the Scrum framework approach, with the stages of product backlog, sprint planning, daily scrum, sprint review, and sprint retrospective. Each stage is implemented iteratively to adapt to user needs and minimize the risk of errors. The results show that the application of the Scrum method results in an accounting information system that is more structured, flexible, and tailored to the store's operational needs. This system simplifies the process of recording transactions, managing inventory, and preparing financial reports quickly and accurately. Thus, the system is able to support more informed decision-making for sporting goods store management